The association between perceived social support and parenting self-efficacy among parents of children aged 0-8 years - Irene N. Fierloos; Dafna A. Windhorst; Yuan Fang; Clemens M. H. Hosman; Harrie Jonkman; Matty R. Crone; Wilma Jansen; Hein Raat (BMC, 2023)
Abstract Strengthening social support has been recognized as a potentially effective strategy to enhance parenting self-efficacy, but empirical evidence is limited. This study examined the association between perceived social support and parenting self-efficacy. Data of 647 parents of children aged 0-8 years, gathered in the CIKEO cohort study in the Netherlands, were analysed. Data were collected between October 2017 and December 2019. Multivariable linear regression models were used to examine the association between social support and parenting self-efficacy. The mean age of the participants was 33.8 years (SD = 4.9); 94.9% mothers. At the start of the study, 15.1% parents perceived low to moderate social support. Parents who experienced lower levels of social support at the start of the study reported lower parenting self-efficacy at follow-up (β: 0.13; 95% CI: 0.05, 0.21), independent of potential socio-demographic confounders. Experiencing an increase in perceived social support during the study period was associated with an increase in parenting self-efficacy (β: 0.15; 95% CI: 0.10, 0.21). Our findings indicate perceived social support is associated with parenting self-efficacy among parents of children aged 0-8 years. Future longitudinal studies need to confirm our findings and may examine which social support interventions are effective in strengthening parenting self-efficacy.